The Path to Understanding: Relation and Solidarity in Whitehead's Metaphysics - Giacone, Alessia (Process studies, 2023)
In this article, I will respond to questions regarding the ontological status of relations by exploring Whitehead's pivotal notion of solidarity, especially focusing on the recently published Harvard lectures. Particularly, I shall investigate how solidarity become a metaphysical law in the development of Whitehead's thought, also exploiting other Whiteheadian works of the same period, such as Science and the Modern World and Religion in the Making. I will attempt to show that the comprehension of an immediate brute fact necessarily requires its metaphysical interpretation as an item in a world with some systematic relation to it. I will thus provide my interpretation on solidarity through a comparison with Hegel's notion of Wirklichkeit.